Modulation of dendritic differentiation by corticotropin-releasing factor in the developing hippocampus - Chen, Yuncai (National Academy of Sciences, 2004)
The interplay of environmental and genetic factors in the developmental organization of the hippocampus has not been fully elucidated. The neuropeptide corticotropin-releasing factor (CRF) is released from hippocampal interneurons by environmental signals, including stress, to increase synaptic efficacy. In the early postnatal hippocampus, we have previously characterized a transient population of CRF-expressing Cajal-Retzius-like cells. Here we queried whether this stress-activated neuromodulator influences connectivity in the developing hippocampal network. Using mice deficient in the principal hippocampal CRF receptor [CRF(1)(-/-)] and organotypic cultures grown in the presence of synthetic CRF, or CRF receptor antagonists, we found robust effects of CRF on dendritic differentiation in hippocampal neurons. In CRF(1)(-/-) mice, the dendritic trees of hippocampal principal cells were exuberant, an effect that was induced in normal hippocampi in vitro by the presence of CRF(1) antagonists. In both cases, total dendritic length and dendritic branching were significantly increased. In contrast, exogenous synthetic CRF blunted the dendritic growth in hippocampal organotypic cultures. Taken together, these findings suggest that endogenous CRF, if released excessively by previous early postnatal stress, might influence neuronal connectivity and thus function of the immature hippocampus.